2018
DOI: 10.1093/toxsci/kfy103
|View full text |Cite|
|
Sign up to set email alerts
|

Prenatal Exposure to DEHP Induces Neuronal Degeneration and Neurobehavioral Abnormalities in Adult Male Mice

Abstract: Phthalates are a family of synthetic chemicals that are used in producing a variety of consumer products. Di-(2-ethylhexyl) phthalate (DEHP) is an widely used phthalate and poses a public health concern. Prenatal exposure to DEHP has been shown to induce premature reproductive senescence in animal studies. In this study, we tested the hypothesis that prenatal exposure to DEHP impairs neurobehavior and recognition memory in her male offspring and we investigated one possible mechanism-oxidative damage in the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 72 publications
2
46
0
Order By: Relevance
“…The second line of evidence for a role for DEHP in metabolic disorder is its effects on neurobehavior, given the interaction of the brain with other key metabolic organs via signaling molecules and neuronal connections at the basis of pathways such as regulation of appetite ( 15 ). Schmidt et al ( 16 ) reported an alteration in food intake in female C3H/N mice after an 8-week exposure to DEHP, and Barakat et al ( 17 ) reported an impairment in neurobehavior and recognition memory in male CD-1 mice after prenatal exposure to DEHP. In addition, inflammation and activation of the immune system have been observed in abdominal obesity and may have a role in the pathogenesis of obesity-related metabolic disorders ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The second line of evidence for a role for DEHP in metabolic disorder is its effects on neurobehavior, given the interaction of the brain with other key metabolic organs via signaling molecules and neuronal connections at the basis of pathways such as regulation of appetite ( 15 ). Schmidt et al ( 16 ) reported an alteration in food intake in female C3H/N mice after an 8-week exposure to DEHP, and Barakat et al ( 17 ) reported an impairment in neurobehavior and recognition memory in male CD-1 mice after prenatal exposure to DEHP. In addition, inflammation and activation of the immune system have been observed in abdominal obesity and may have a role in the pathogenesis of obesity-related metabolic disorders ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that treatment of pregnant females with DEHP resulted in nonlinear, U-shaped, dose-response effects on number of pups and sex ratio in newborn offspring 24,33,[71][72][73][74] . Our findings indicate that the pattern of nonlinear dose-response seen in the first generation is transmitted to the future generations.…”
Section: Discussionmentioning
confidence: 99%
“…As an endocrine-disrupting chemical (EDC), DEHP disrupts the reproductive system and acts as an anti-androgen in both females and males [22][23][24] . DEHP metabolites have been detected in amniotic fluid 19 , umbilical cord blood 25 , and other bodily fluids 26 , indicating that humans are exposed to DEHP as early as fetal stage of their development 27 .…”
mentioning
confidence: 99%
“…This suggests that other mechanisms, unrelated to the hypothesised impairment of brain masculinisation, may also drive behavioural changes induced by DEHP and other phthalates. According to Barakat et al, the anxiogenic effects of prenatal DEHP exposure may be related to increased hippocampal degeneration. However, we did not see differences between control and DiPeP exposed animals in relation to the time spent in open arms, indicating that DiPeP exposure during critical periods does not promote anxiety‐like behaviours in males under our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not see differences between control and DiPeP exposed animals in relation to the time spent in open arms, indicating that DiPeP exposure during critical periods does not promote anxiety‐like behaviours in males under our experimental conditions. It is important to note that Barakat et al assessed the neurobehavioural effects of prenatal DiPeP exposure in 16‐22 weeks old rats, whereas our animals were tested at younger ages.…”
Section: Discussionmentioning
confidence: 99%